Epidemic intelligence needs of stakeholders in the Asia–Pacific region (Western Pacific Surveillance and Response, 2018)
Objective: To understand the global outbreak surveillance needs of stakeholders involved in epidemic response in selected countries and areas in the Asia–Pacific region to inform development of an epidemic observatory, Epi-watch.Methods: We designed an online, semi-structured stakeholder questionnaire to collect information on global outbreak surveillance sources and limitations from participants who use epidemic intelligence and outbreak alert services in their work in government and nongovernment organizations in the Asia–Pacific region.Results: All respondents agreed that it was important to remain up to date with global outbreaks. The main reason cited for following global outbreak news was as an early warning for serious epidemics. Mainstream media and specialist Internet sources such as the World Health Organization (n = 54/91; 59%), the Program for Monitoring Emerging Diseases (ProMED)-mail (n = 45/91; 49%) and the United States Centers for Disease Control and Prevention (n = 31/91; 34%) were the most common sources for global outbreak news; rapid intelligence services such as HealthMap were less common (n = 9/91; 10%). Only 51% (n = 46/91) of respondents thought that their sources of outbreak news were timely and sufficient for their needs.Conclusion: For those who work in epidemic response, epidemic intelligence is important and widely used. Stakeholders are less aware of and less frequently use rapid sources such as HealthMap and rely more on validated but less timely traditional sources of disease surveillance. Users identified a need for more timely and reliable epidemic intelligence.